Investigation on the Students’ Perceptions of the Arabic Speaking Skills toward the Contextual Teaching Learning Implementation - Wahdah, Nurul; Mubarak, Mahfuz Rizqi; Ilmiani, Aulia Mustika; Almuddin, Azhani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study explores the students' perceptions of the results of Contextual Teaching Learning (CTL) implementation in the Arabic speaking skill lectures based on the typical characteristics of the Student-Centered Learning approach in their class. The researchers need information on whether implementing a method in the context of the Arabic language skills in tertiary institutions meets the Student-Centered Learning approach criteria. In addition, most of the research still focuses on describing the method's implementation. It ignores the achievement of the method on the criteria for the Student-Centered Learning approach. This study uses an exploratory investigation to understand implementation results in-deeply. Thirty AFL students with different cultural backgrounds completed a questionnaire about their perceptions of successful implementation. The findings reveal that implementing CTL in teaching the Arabic speaking skills meets the typical characteristics of the Student-Centered Learning approach. Moreover, some students also give positive suggestions to achieve a more optimal standard. Therefore, this study provides some recommendations and directions for further studies.